OPTIMASI PROSES PRODUKSI KERAMIK LANTAI 60X60 GRANITE MENGGUNAKAN METODE LEAN SIX SIGMA DI PABRIK KERAMIK TANGERANG - Hartono, Hartono; Frenando, Manendra; Supono, Joko (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
The main objective of this study is to identify and reduce product defects occurring during the production process. Data was collected from January to December 2023, with an initial defect rate of 8.65%, equivalent to 86,500 defects per million opportunities (DPMO). Through the application of the Lean Six Sigma method, the defect rate was successfully reduced to 6.16%, or 61,600 DPMO. The initial Sigma level was 3.82 and increased to 4.10 after improvements. This approach involves several key stages: Define, Measure, Analyze, Improve, and Control (DMAIC). In the Define stage, the problem is clearly defined, including identifying the most frequent types of defects such as cracks, surface blemishes, and size variations. In the Measure stage, data is collected and analyzed to identify problematic areas, using statistical tools like histograms, Pareto charts, and control charts. In the Analyze stage, an in-depth analysis is conducted to find the root causes of defects through methods like the 5 Why's and fishbone diagram. In the Improve stage, solutions are implemented to address the root causes, such as adjusting machine parameters, retraining employees, and enhancing raw material quality. In the Control stage, steps are taken to ensure that the improvements made can be sustained in the long term by implementing regular monitoring procedures and quality audits. Keywords : Lean Six Sigma, Product Defect, Production Process, Quality Product, DMAIC, Floor Tile.